Penerapan Metode Learning Starts With A Question Untuk Meningkatkan Keaktifan Belajar Mata Pelajaran FIQIH - Yaqin, Firdaus Ainul; Herwati, Herwati; Fadilah, Rini Nur (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2022)
Abstract This observation is a way to advance student learning activities at MTS Darut Tauhid Tanjung Sari Krejenga, in the FIQIH lesson on the learning starts with a question, the researcher uses qualitative analysis which includes the learning starts with a question method. Which includes the learning starts with a question method., which is to increase student learning activities which aredirected to independent in learning by making questions given by the teacher. So this study proves that the learning model does not make it difficult for students to study. Keywords: Learning Model, student Learning, FIQIH